Pre-Service Primary School Teachers’ Understanding of Biogeochemical Cycles of Elements - Luka Ribič; Iztok Devetak; Robert Potočnik (Education Sciences)
Understanding environmental issues such as biogeochemical cycles of substances on a local and global level is important in order to be able to act responsibly and sustainably. Inadequate teacher training has proven to be the main reason why environmental education has failed to reach its full potential. The aim of the present study is therefore to investigate students’ level of knowledge about biogeochemical cycles in relation to their secondary school achievements in chemistry, biology, and physics, their individual interest for learning these topics, and their self-esteem regarding cycles of substances on Earth. A total of 145 undergraduate pre-service primary school teachers attending their first or third year of an undergraduate teacher education program at the Faculty of Education, University of Ljubljana, in 2024 participated in this quantitative study, which uses the causal non-experimental method of pedagogical research. The data were collected using a three-tier achievement test and a paper–pencil questionnaire, which were both developed by the researchers. The results show that pre-service primary school teachers possess roughly adequate knowledge of the environmental topic of biogeochemical cycles. Their individual interest and self-esteem related to learning biogeochemical cycles were found to be significant predictors of their performance in an achievement test on biogeochemical cycles. Their final grade in biology may also be a significant predictor of their knowledge of this topic. Finally, pre-service primary school teachers’ misconceptions related to the topic of biogeochemical cycles were determined. Although the number of their misconceptions on this topic is low, teachers’ environmental education nevertheless needs to be improved in order to optimize their work in the classroom and help environmental education reach its full potential.